2022
DOI: 10.1128/spectrum.00465-22
|View full text |Cite
|
Sign up to set email alerts
|

Development of the First Tractable Genetic System for Parvimonas micra, a Ubiquitous Pathobiont in Human Dysbiotic Disease

Abstract: Parvimonas micra is among the most highly enriched species at numerous sites of mucosal dysbiotic disease and is closely associated with numerous cancers. Despite this, little is known about P. micra pathobiology, which is directly attributable to its longstanding genetic intractability.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Periodontal disease has previously been described as having inflammophilic bacterial communities, meaning the species present thrive under inflammatory conditions, allowing them to outcompete other species 34, 35 . Parvimonas and Fusobacterium , as part of microbial cohorts, were shown to reduce neutrophil killing via dampening of reactive oxygen species production, and produced proteases to degrade immunoglobulins and complement proteins, reducing phagocytosis by host immune cells 35 . Both Parvimonas and Fusobacterium have been shown to induce inflammatory cytokines like IL-6 and IL-8 35, 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodontal disease has previously been described as having inflammophilic bacterial communities, meaning the species present thrive under inflammatory conditions, allowing them to outcompete other species 34, 35 . Parvimonas and Fusobacterium , as part of microbial cohorts, were shown to reduce neutrophil killing via dampening of reactive oxygen species production, and produced proteases to degrade immunoglobulins and complement proteins, reducing phagocytosis by host immune cells 35 . Both Parvimonas and Fusobacterium have been shown to induce inflammatory cytokines like IL-6 and IL-8 35, 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Parvimonas and Fusobacterium , as part of microbial cohorts, were shown to reduce neutrophil killing via dampening of reactive oxygen species production, and produced proteases to degrade immunoglobulins and complement proteins, reducing phagocytosis by host immune cells 35 . Both Parvimonas and Fusobacterium have been shown to induce inflammatory cytokines like IL-6 and IL-8 35, 36 . Fusobacterium was shown to invade the epithelial barrier in appendicitis 25 .…”
Section: Discussionmentioning
confidence: 99%
“…We identified a highly diverse MecA interactome and were able to use this information to develop and validate a new split luciferase complementation assay (SLCA) useful for monitoring PPI in live bacteria. Our SLCA approach employed a synthetic red-shifted Renilla luciferase variant of RLuc8 (6164) called Green Renilla (RenG), which we have previously demonstrated to yield exceptionally high activity in a variety of bacterial species (46,65). Besides its robust luminescence output, RenG is also particularly well suited for SLCA applications due to its small size (36 kDa) and monomeric functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Carlsson et al ( 1993 ) investigated the proteolytic ability 37 oral species and found that Peptostreptococcus micros ( Parvimonas micra ) and Fusobacterium nucleatum have a high capacity to degrade tripeptides and produce H 2 S. This behaviour is only found in opportunistic pathogens including Escherichia coli and Pseudomonas aeruginosa . Parvimonas micra is also the most common source of sepsis produced by GPAC (Higashi et al, 2022 ). The proteolytic capabilities of Parvimonas micra and Fusobacterium nucleatum are found in acute apical abscesses and seem to support mucosal dysbiosis also related to colon rectal cancer (George et al, 2016 ; Higashi et al, 2022 ; Siqueira & Rôças, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Parvimonas micra is also the most common source of sepsis produced by GPAC (Higashi et al, 2022 ). The proteolytic capabilities of Parvimonas micra and Fusobacterium nucleatum are found in acute apical abscesses and seem to support mucosal dysbiosis also related to colon rectal cancer (George et al, 2016 ; Higashi et al, 2022 ; Siqueira & Rôças, 2009 ). Interestingly, the combination of Parvimonas micra and Peptostreptococcus stomatis in combination with Fusobacterium nucleatum , and Solobacterium morei are potential biomarkers of colorectal cancer (Yu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%